How to fly (in ten thousand easy lessons) : poetry - Kingsolver, Barbara (Harper, an imprint of HarperCollins Publishers, 2020)
In her second poetry collection, Barbara Kingsolver offers reflections on the practical, the spiritual, and the wild. She begins with "how to" poems addressing everyday matters such as being hopeful, married, divorced; shearing a sheep; praying to unreliable gods; doing nothing at all; and of course, flying. Next come rafts of poems about making peace (or not) with the complicated bonds of friendship and family, and making peace (or not) with death, in the many ways it finds us. Some poems reflect on the redemptive powers of art and poetry itself; others consider where everything begins. Closing the book are poems that celebrate natural wonders--birdsong and ghost-flowers, ruthless ants, clever shellfish, coral reefs, deadly deserts, and thousand-year-old beech trees--all speaking to the daring project of belonging to an untamed world beyond ourselves.